Nursing Practice - Dzuda, Simbarashe Christopher; Tsilosani, Giorgi (Caucasus Journal of Health Sciences and Public Health, 2018)
Nurses play a vital role in the delivery of healthcare services globally. They are the backbone of the healthcare delivery system, and without their contribution healthcare services would not be delivered efficiently. The contribution of physicians and other healthcare professionals are also equally important, as they also contribute towards the provision of efficient healthcare services. Nurses can perform several roles including being an educator, counselor, communicator, patient advocate as well as a caregiver. They often spend more time with patients, assisting in the rehabilitation, promotion and restoration of health. The essential fundamental of practice for the registered nurse is to deliver complete, patientfocused care. All the actions and activities of a nurses are guided by six values which are care, compassion, courage, communication, competence and commitment. The nursing process, which is a series of structured steps is also utilized by nurses to provide excellent care. There are five phases in the process, and they include assessment, diagnosis, outcome identification & planning, implementation, and evaluation. Assessment includes a physical assessment, and they are instrumental in the laboratory assessment. Essentially, in the nursing practice the nurse aims to diagnose and treat actual or potential health problems. Nurses make up part of the medical team responsible for decision making. Other members include the physician, anesthesiologist and the medical technician.